NBO - NEDA and AIM studies on the interactions between benzocryptand [222B] and Li+, Na+, K+ and Ca2+ - Behjatmanesh–Ardakani, R.; Arab, M.D.; Saleem, A.; Kotena, Z.M.; Mohamad, S.B. (Global Research Online, 2016)
Cryptands are widely studied due to their potential applications in various chemical and physical processes especial as models for biological systems. We employed B3LYP density functional theory with 6-311G* basis set to optimize the geometries and subsequently calculate binding energies (in the gas phase) of the ligand based on benzocryptand [222B] bounded to alkali metal univalent cations such as Li+, Na+, K+ and alkaline earth divalent cation such as Ca2+. Atoms in molecules (AIM) approach, natural bond orbital (NBO), and natural energy decomposition analysis (NEDA) were used to understand the nature of the host-guest interaction. From AIM theory, all interactions between donor atoms of [222B] ligand and central ions are referred to as a closedshell based on the Laplacian data, and the interactions are totally electrostatic, based on both the Laplacian and total energy, which are positive. From NBO analysis, (L-Ca2+) complex has the highest the stabilization energy. Additionally, the NEDA analysis suggests that the order relative of energy for the alkali metal complexes is electrostatic > polarization > charge transfer, while that for the alkaline earth metal complex is polarization> electrostatic > charge transfer. The finding results show that all donor atoms in [222B] ligand were involved with Ca2+ in (L-Ca2+) complex, while (L-Li+) complex does not interact with the nitrogen and the oxygen adjacent to benzene. We proposed the alkali metal univalent cations such as lithium which has the smallest radius only draw four oxygen atoms around the cavity of the [222B] ligand, while alkaline earth metal divalent cation (calcium) with a higher charge density is able to bond with six oxygen atoms and two nitrogen atoms. Compared to the ionic radius, the charge density is a more dominant factor which governs the binding of the alkali and alkaline earth metal ions to the [222B] ligand.